Anaerobic Co-Digestion of Bread Waste and Sewage Sludge for Methane Production - Ching Wong Yee; Johori Nur Zulaikha Hazwani binti; Hasan Hasan Abdellatif (E3S Web of Conferences)
The purpose of this study is to develop a lab-scale model for energy self-sufficiency via the promotion of the generation of sustainable renewable energy from bread waste and sewage sludge to biogas. Most of the garbage consisting of bread and sewage sludge is typically disposed of in landfills, which can result in substantial health and environmental problems due to the release of gaseous substances. As a result of this, the research endeavors to make use of sewage sludge and bread wastes as substrates to produce methane. A pH meter and a drying oven were used, respectively, to analyze each substrate’s pH level as well as its dry weight, total solids, and volatile solids content. A methane gas detector was used on each sample to check for the presence of methane. The recorded pH is within the optimal range as it is between 6.9 and 7.2 for the substrates, bread waste, and sewage sludge as well as both ratios of the mixtures before and after the anaerobic co-digestion process. Following three to four days of cultivation using the streaking and spread culture method on nutrient agar, the microorganisms Saccharomyces cerevisiae and Pseudomonas aeruginosa were isolated from the bread waste and sewage sludge, respectively. The methane gas detector registered a value of 9999 ppm, which is 20% LEL.